Does a renal diet question prompt sheet increase the patient centeredness of renal dietitian outpatient consultations?. Issue 8 (August 2020) - Lambert, Kelly; Lau, Tsz Kwan; Davison, Sarah; Mitchell, Holly; Harman, Alex; Carrie, Mandy
Highlights: Patients often report they do not know what questions to ask the dietitian. In this study, a QPS was mailed to the patient prior to the appointment. The RIAS was used to evaluate the 'patient centredness' of the interaction. The QPS increased the patient centeredness of the consultation with the dietitian. Increased conversation for education and counselling did not increase consult time. Abstract: Objective: Effective communication is fundamental to helping patients change behaviour. Few studies have operationalised how to quantify and improve the patient centeredness of communication during the dietitian outpatient consultation. We sought to evaluate the impact of a renal diet question prompt sheet (QPS) on patient centeredness (PC) in dietitian outpatient clinics and describe the impact of a renal diet QPS on the volume and pattern of communication between dietitians (n = 4) and patients/carers (n = 24, n = 11). Methods: The Roter Interaction Analysis System was used to compute a PC index, the volume communication (number of questions and utterances) and categorise dietitian communication. Results: The QPS was associated with significant improvements in the PC of communication (p = 0.004 and p = 0.001), without increasing the volume of communication. The QPS was also associated with an increase in the total number of questions asked (p < 0.0001) especially from patients (p = 0.0009); and an increase in the volume of communication devoted to education and counselling (p < 0.0001). Conclusions: This study describes a promising intervention to increase the patient centeredness of dietetic consultations in an outpatient setting. Practice implications: Whilst simple in design, the use of a QPS had a large effect on how patients and carers interact with the dietitian in the outpatient setting.